IDENTIFIKASI KANDUNGAN KIMIA DENGAN GC-MS DARI FRAKSI UMBI BAWANG BATAK (Allium chinense G.Don) - Sylvia Rizky Prima (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2024)
Batak onions (Аllium chinense G. Don) are an onion that local from Samosir Island, North Sumatera. This plant is used empirically as a cooking spice. Previous research reported that this plant has several bioactivities such as antimicrobial. This research aims to determine the chemical content of several fractions of Batak onion bulbs using the Gаѕ Сhrоmаtоgrарhy Mаѕѕ Ѕресtrоmеtry (GС-MЅ) method. Extraction was carried out using a maceration technique and continued with a fractionation process using the solvents n-hexane, ethyl acetate and butanol. The results of the analysis showed that the compound content of several of the onion tuber fractions was 13 compounds obtained h from the n-Hexane fraction, 9 compounds obtained from the ethyl acetate fraction, and having 7 y compounds which is obtained from the butanol fraction. Oleic acid compound is the most dominant compound contained in Batak onion bulbs from local Samosir island, with the percentage of its content in the n-hexane, ethyl acetate and butanol fractions being 22.05%, 52.42% and 59.38%, respectively.